A dimensão ontológica da educação da infância para além da Base Nacional Comum Curricular: análise a partir da pedagogia histórico-crítica - Vasconcelos, Sávio Silva (2023)
This paper aims to analyze the early childhood education from the Common National Curricular Base (BNCC), from a perspective that goes beyond the limits of idealistic normative legality, expressed in the texts of the Brazilian education law, with a view to an ontological understanding of the educational reality of the concrete child, based on the foundations of Critical Historical Pedagogy. To better develop this theme, we pose the following questions as research problems: 1) What philosophical and political foundations guide the proposal of the Common National Curricular Base (BNCC) for Early Childhood Education? 2) Is it possible to build an educational alternative that, even within a counter-hegemonic perspective, can overcome the current proposal for Early Childhood Education? The development of this study was based on the methodological aspects of historical-dialectical materialism, from theoretical studies, bibliographic review (texts, articles, dissertations, theses, and books) and document analysis (legal devices and official documents), with a qualitative focus. The categories of analysis: ontology, childhood being, childhood education and subject-proletarian of the future, are based on a socio-historical reality situated in the debate about human sociability in the capitalist production mode. Given the nature of this investigation, it was necessary to turn to Marxian and Marxist literature to find the theoretical contributions needed to criticize school education as an instrument for reproducing the sociability of capital, of which the National Common Base Curriculum is a constituent element.The results are defined as follows: in the prevailing social form, education is understood as an instrument of production and economic development. The constitution of subjectivities of individuals from school, from an early age, is based on the assumption of the formation of productive capacity for alienated work, taking as elements the knowledge, skills and abilities that are effective for the maintenance of the hegemonic dynamics of capital. It is in this sense that the BNCC, specifically the stage of early childhood education, projects in the childhood being the subject-proletarian of the future. Thus, Critical Historical Pedagogy has the ontological assumptions of understanding the sociability of the capital and the foundations of the critical revolutionary overcoming of the conception of bourgeois education.